The province of jurisprudence determined. - Austin, John, 1790-1859 (Cambridge Texts in the History of Political Thought., 1995)
The Province of Jurisprudence Determined (1832) is a classic of nineteenth-century English jurisprudence, a subject on which Austin eventually had a profound impact. His book is primarily a meticulous exposition of most of the core concepts of his legal philosophy, including his command conception of law, his separation of law and morality, and his theory of sovereignty. Almost a quarter of the book consists, however, of an interpretation and defence of the principle of utility." "This edition includes the complete and unabridged text of the fifth (1885) and last edition. The comprehensive introduction discusses Austin's life, the main themes of his book, leading criticisms of his ideas, and recent interpretations of his legal philosophy. The edition also includes and up-to-date bibliography and biographical synopses of the principal figures mentioned in the text.